Synergism effect of Murraya koneigii and Piper betle leaves extracts on antibacterial activity against Gram Positive bacteria - Putri Shareen, Rosman; Syarmilla Ezza, Ismail; Mohd Khairul, Bahri; Nur Syazdiyana, Mohd Azmali; Tan, Suat Hian (Penerbit Akademia Baru, 2022)
Antimicrobial resistance has become the major threat to the health worldwide. It has lead to the ineffective impact of the ability of the substance or antibiotics to kill the bacteria. Therefore, there is a need to find a new alternative to overcome the problem by using natural products. In this study Piper betle (P. betle ) and Murraya koenigii (M. koenigii) leaf extracts were used to measure their synergism effect towards antimicrobial treatments. Previous study has shown that both plants has shown their ability in inhibiting the growth of bacteria separately. Three different concentration ratios of the synergised leaf extracts were used with 1:1(P.betle:M. koenigii) ratios, 2:1 (P.betle:M. koenigii) ratios and 1:2 (P.betle:M.koenigii) ratios. The synergised leaf extracts was at the highest inhibition zone with combination of 2:1 ratio of P.betle and M. koenigii with 22.6mm. However, it does not have the greater inhibition ability as compared to the P.betle leaf extract with 28.1mm. Therefore, from the study, antagonism effect was discovered when both plant extracts were combined.